2016
DOI: 10.1111/ijac.12616
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of morphology and photoluminescence properties of gehlenite: Eu glassy phosphors

Abstract: In this study, gehlenite: Eu glassy powders were synthesized from two common Si sources, silicon tetraethyl orthosilicate (TEOS) and silicon acetate (SiA), using spray pyrolysis. Its morphology and chemical composition were studied. The morphological results suggested that the SiA‐derived powder contained more porous particles than the TEOS‐derived powder. The two gehlenite powders thus formed were found to have similar chemical compositions. Accordingly, porous gehlenite: Eu glassy phosphor seems to exhibit s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…In this study, the Type II particles had more porosity than Type I particles, and therefore, Type II particles (836 nm) exhibited the larger particle size than that of Type I particles (713 nm). A similar result has been reported in our previous study [22].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, the Type II particles had more porosity than Type I particles, and therefore, Type II particles (836 nm) exhibited the larger particle size than that of Type I particles (713 nm). A similar result has been reported in our previous study [22].…”
Section: Discussionsupporting
confidence: 93%
“…In the previous work, there are few reports on gehlenite (Ca 2 Al 2 SiO 7 ) doped Eu phosphors using spray pyrolysis method [19]. e obtained result was amorphous phase and the result showed that red mission was obtained.…”
Section: Introductionmentioning
confidence: 96%
“…The SP method has been used to circumvent these issues [24,27]. Compared with the aforementioned techniques, SP offers several advantages, including less contamination [24], compatibility with the continuous process [28], fast processing time (∼1 h) [27], and morphological flexibility [29,30]. Furthermore, several high-purity micron-sized phosphor materials of various morphology were successfully synthesized using this method.…”
Section: Introductionmentioning
confidence: 99%
“…Yttrium borates and yttrium oxide series with unique hexagonal YBO 3 and cubic oxide phases were prepared by SP, contributing to efficient luminescence and a prolonged decay time [29]. In addition, we successfully prepared solid, hollow, and porous Eu-doped gehlenite using SP [27] and demonstrated its superior photoluminescence (PL) properties [30]. Therefore, this study attempts to prepare a green phosphor with a narrow wavelength range by SP.…”
Section: Introductionmentioning
confidence: 99%